Intertextual Study Of The 'Aqidah Al-'Awām - roch aris hidayat (Center for Research and Development of Religious Literature and Heritage, 2019)
This study aimed to describe the conception of aqidah (creed) in the book ‘Aqīdah al-‘Awām by Sayyid Ahmad Al-Marzuqi. This book is taught in Al-Ihya Ulumaddin Islamic Boarding School, Cilacap, Central Java. The teaching of the book ‘Aqīdah al-‘Awām in Al-Ihya Ulumaddin Islamic Boarding, Cilacap, is one of the efforts to keep and maintain the aqidah of the students in the boarding school. The method used in this study was philology which was conducted in several steps, namely; identifying manuscript, describing manuscript, and conducting a content analysis of the manuscript. The results suggested that the conception of aqeeidah in the Book ‘Aqīdah al-‘Awām includes knowledge of the attributes of Allah (God), of Prophets/Messengers, Angels, Holy Book, and Day of Judgment. Aqeedah is a basic element of faith of a Muslim. Aqeedah must always be kept and maintained so as not to be lost or destructed by the influence of the environment. In addition, the book ‘Aqīdah al-‘Awām also contains the stories of the family of Prophet Muhammad, and Isra' Mi'raj. The matan of this book was written by Sayid Ahmad al-Marzuqi al-Maliki. This book has been given for explanations or comments (syarah) by various parties, among them, Sheikh Nawawi al-Bantani with Nuruz Zalam book, Bisri Mustafa with Rawihat al-Aqwam book, and Muhammad Ihya' Ulumiddin with the Syarah ‘Aqīdah al-‘Awām book. In addition, based on this book, there has also been written another book of which contents were taken from some of the contents of the book ‘Aqīdah al-‘Awām, for example, the Niyat Ingsun Ngaji book written by KH. Badawi Hanafi from Al-Ihya Ulumaddin Islamic Boarding School, Cilacap, Central Java. Keywords: philology, ‘Aqīdah al-‘Awām book, Islamic Boarding School, syarah, Al-Ihya Ulumaddin